Integration of Al-Kindi's Holistic Education Philosophy and Its Relevance to the Implementation of the Independent Curriculum in Madrasah Aliyah - A. Heris Hermawan; Mulyawan Safwandy Nugraha; Nadira Salsabila (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research examines the integration between Al-Kindi's holistic education philosophy and the implementation of the Independent Curriculum in Madrasah Aliyah, highlighting the need for a more inclusive and holistic educational paradigm. The background of this research is rooted in contemporary challenges in education that demand a holistic approach to curriculum development and teaching methodologies. The purpose of this paper is to analyze the suitability and potential synergy between the two approaches in the context of modern Islamic education. This research used a qualitative research paradigm with a literature approach, where data was collected from various literature related to the topic of discussion. The data is then verified and analyzed systematically to be presented in a structured manner. Key findings suggest that this integration supports the development of student-centered curricula and enhances diverse and interactive teaching methodologies. Implications include the need for teacher professional development, adequate resource allocation, and strategic partnership building to support the implementation of holistic approaches in education.